Tumor immunoevasion via acidosis-dependent induction of regulatory tumor-associated macrophages. (December 2018) - Bohn, Toszka; Rapp, Steffen; Luther, Natascha; Klein, Matthias; Bruehl, Till-Julius; Kojima, Nobuhiko; Aranda Lopez, Pamela; Hahlbrock, Jennifer; Muth, Sabine; Endo, Shogo; Pektor, Stefanie; Brand, Almut; et al.
Abstract Many tumors evolve sophisticated strategies to evade the immune system, and these represent major obstacles for efficient antitumor immune responses. Here we explored a molecular mechanism of metabolic communication deployed by highly glycolytic tumors for immunoevasion. In contrast to colon adenocarcinomas, melanomas showed comparatively high glycolytic activity, which resulted in high acidification of the tumor microenvironment. This tumor acidosis induced Gprotein–coupled receptor–dependent expression of the transcriptional repressor ICER in tumor-associated macrophages that led to their functional polarization toward a non-inflammatory phenotype and promoted tumor growth. Collectively, our findings identify a molecular mechanism of metabolic communication between non-lymphoid tissue and the immune system that was exploited by high-glycolytic-rate tumors for evasion of the immune system. Tumors can vary in both their control by immunosurveillance and their glycolytic activity. Bopp and colleagues demonstrate that highly glycolytic tumors acidify their microenvironment and use this to initiate a mechanism of localized immunosuppression.